The effect of perceived parenting styles on religion attitude and emotional intelligence of high-school girl students - Monireh Amiri; Anahita khodabakhshi koolaee; Zabih Pirani (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here. Background and Objectives: Religious attitudes and emotional intelligence of students can be changed under parenting styles. Propose of this study was to investigate the effect of perceived parenting styles on religion attitude and emotional intelligence of high-school girl students in 2014. Materials and Methods: The statistical society of research was the high-school girls in 2014 in Arak city, 87 of them were selected by multistage cluster sampling. Participants answered the two questionnaires including emotional intelligence, religion attitude (Baraheni) questionnaires. The mothers of participants replied to parenting styles questionnaire, Baumrind questionnaire. The data were analyzed by multi-variety regression and Pearson correlation. Results: The results showed permissive parenting style had negative significant correlation with religion attitude and emotional intelligence. In addition, authoritarian parenting had no relationship with the emotional intelligence, while the authoritative parenting style had positive correlation with emotional intelligence and religion attitude of students.  Conclusion: The findings revealed that the authoritative parenting leads to more emotional intelligence and religion attitude of students that facing the problems life while in the case of permissive parenting is the opposite. Keywords: Parenting Styles, Religion Attitude, Emotional Intelligence, Girl Students For downloading the full-text of this article please click here.